2018
DOI: 10.1111/ijpo.12491
|View full text |Cite
|
Sign up to set email alerts
|

Can waist circumference provide a new “third” dimension to BMI when predicting percentage body fat in children? Insights using allometric modelling

Abstract: Summary Introduction Body mass index (BMI) is often criticized for not being able to distinguish between lean and fat tissue. Waist circumference (WC), adjusted for stature, is proposed as an alternative weight status index, as it is more sensitive to changes in central adiposity. Purpose The purpose of the study is to combine the three dimensions of height, mass, and WC to provide a simple, meaningful, and more accurate index associated with percentage body fat (BF%). Methods We employed a four independent sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
1
10
0
1
Order By: Relevance
“…Since then, hundreds of publications report associations between WHtR and health outcomes across most of the lifespan and in several different race/ethnic groups . A challenge to the WHtR comes from studies published over the past 5 years suggesting scaling exponents for height of less than 1.0 as a means of making the waist circumference‐stature index independent of height …”
Section: Waist Circumferencementioning
confidence: 99%
See 1 more Smart Citation
“…Since then, hundreds of publications report associations between WHtR and health outcomes across most of the lifespan and in several different race/ethnic groups . A challenge to the WHtR comes from studies published over the past 5 years suggesting scaling exponents for height of less than 1.0 as a means of making the waist circumference‐stature index independent of height …”
Section: Waist Circumferencementioning
confidence: 99%
“…body weight/height 2 ) is relatively straightforward, less clarity surrounds the most appropriate index for waist circumference that reflects excess adiposity and health risks. Specifically, current obesity and metabolic syndrome guidelines promote the use of absolute waist circumference with sex and ethnicity‐specific cut‐off values, and a large and growing literature advances observations surrounding the waist circumference/height ratio (WHtR) or other similar waist circumference‐stature ratios . Should WC be adjusted for height (Ht)?…”
Section: Introductionmentioning
confidence: 99%
“…Indeed by incorporating the WC term into the model (Equation (1)), we reveal that WC provides a valuable new insight. i.e., a new “third” dimension associated with predicting CRF as well as excess fat [ 24 ]. Note that the SES parameter in Table 2 is negative indicating that the children from more affluent parents are less fit.…”
Section: Discussionmentioning
confidence: 99%
“…A multiplicative model with allometric body-size components, originally proposed by Nevill and Holder [ 23 ] and recently adopted by Nevill et al [ 24 ], was used to explore differences between categorical (e.g., sex, residential location) and associations with body-size variables, given by VO 2max (mL·kg −1 ·min −1 ) = M k1 × H k2 × WC k3 exp(a + b·age + c·age 2 + d·SES) × ε, where “a” is the constant intercept term, M = mass, H = height, WC=waist circumference, SES = socioeconomic status points and “ε” is a multiplicative, error ratio that assumes the error will be in proportion to VO 2max (mL·kg −1 ·min −1 ). The inclusion of height, mass and WC within the model is important as previous research has demonstrated that inclusion of all three of these anthropometric variables identifies people at risk of excess fatness and cardiometabolic risk more effectively than height and mass alone.…”
Section: Methodsmentioning
confidence: 99%
“…1 This count is still based on Body Mass Index (BMI) even though the latest progress showed that the measurement of waist circumference is a more precise method of determining obesity. 1,5 The children who got obesity tend to five times higher than normal children who suffer obesity while being adults. 6 It is dangerous because of many complications within obesity such as cardiovascular disease, diabetes mellitus type 2, hypertense, endothelium disfunction, and several types of cancer such as colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%